Pengaruh ROA, EPS dan DER Terhadap Harga Saham Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Periode 2018-2021 - Kristina Adriani; Cindy Marta Fransiska Saragih; Fadina Garora Harahap; Tiona Siagian; Helman Helman; Hazmanan Khair (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In connection with this study there are objectives, among others, to test the impact of ROA, EPS and DER effect on stock prices. This type of research is based on a quantitative approach. The population used in this study is the consumer goods sector manufacturing companies listed on the IDX for the period 2018-2021 as many as 18 companies and a sample of 6 companies and then a total of 24 reports of observations. The results of the study, among others, ROA, DER partially does not affect the stock price, eps partially positive effect on stock prices and then simultaneously ROA, EPS and DER simultaneously positive effect on stock prices.